Esquina da pesquisa: uma proposta para educar pela pesquisa os alunos dos cursos de licenciatura da modalidade EaD da UFMA - OLIVEIRA, Luiza Carvalho de (2016)
This research describes the process of designing, developing and validating an educational digital material called: Research Corner - which aims at supporting students taking distance education Bachelor‟s degrees at UFMA with the development of skills needed to research, based on the methodological approach of Educating by Searching by Pedro Demo (2011c). The work is the result of a multi-methodological study which fits into the so-called Development Methodologies (Coutinho, KEYS, 2001; ARREDONDO, 2014), with quantitative and qualitative approaches that contemplated the processes of designing, developing and evaluating the educational quality of the prototype, and involving a bibliographical and exploratory study in order to define: the philosophical and pedagogical framework as well as its methodological theory; the development of the educational design and prototype; and its ergonomic-educational evaluation, conducted through prospective tests with the user, based on the Ergonomic Criteria of Usability supported by Christian Bastien and Dominique Scapin (1993); and semi-structured interview based on the criteria of formal and political quality defined by Demo (2005a; 2006), both of them performed with an audience of five (5) teachers who work in distance education. Instruments and research techniques were analyzed using simple statistics and content analysis accordingly. Since it is a transdisciplinary research which incurs a nonlinear theoretical and methodological approach as well as a recursive one, a comprehensive literature review was needed in order to design the prototype and it included: (1) the relationship between science and the teaching and learning process with a reconstructive and interdisciplinary approach to design learning; (2) the university and its relationship with the research; (3) online learning and its possibilities in the context of complexity; and (4) Educating by Searching that underlies this study as a scientific and educational principle. The data collected helped us to understand that (a) the interface and the pedagogical proposal of the educational digital material developed are; in fact, a singular strategy for the teaching and learning process regarding research, and (b) that it can be incorporated as a daily attitude, both in its formal and political forms.